2020
DOI: 10.1016/j.jclepro.2019.118975
|View full text |Cite
|
Sign up to set email alerts
|

From the Celtic Tiger to the Celtic Phoenix: The metabolic profile of Ireland and the main drivers of energy change

Abstract: In this paper, the metabolic profile of Ireland and the main drivers of energy variations are analysed for the period 1998-2014. By considering the years that extend from the Celtic Tiger to the Celtic Phoenix, the socioeconomic and energy variables are analysed during periods of economic growth and recession. The main objective is to investigate how demographic and economic trends have influenced the energy used across different levels of analysis. The potential implications of economic growth and population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…32 driven by structural changes and implementation of energy efficiency action plans, has contributed to reducing the energy used in relation to gross domestic product and human time. 34 ul Husnain et al indicated short-run coherence among energy consumption and economic growth of all the top 10 energy-consuming countries. Long-run dependence between energy consumption and economic growth exists in the case of China with a mostly leading role of energy consumption over economic growth.…”
Section: Research On the Influencing Factors Of Energy Consumptionmentioning
confidence: 99%
“…32 driven by structural changes and implementation of energy efficiency action plans, has contributed to reducing the energy used in relation to gross domestic product and human time. 34 ul Husnain et al indicated short-run coherence among energy consumption and economic growth of all the top 10 energy-consuming countries. Long-run dependence between energy consumption and economic growth exists in the case of China with a mostly leading role of energy consumption over economic growth.…”
Section: Research On the Influencing Factors Of Energy Consumptionmentioning
confidence: 99%
“…We should note that there are no studies at the regional level of MuSIASEM inside a country. They exist to compare countries [24][25][26][27], to analyze the evolution of a country [28][29][30] or those that exist focus on a specific region [31,32]. For this reason, this work presents a novel tool for electricity planning and focuses on performing a multilevel and multiregional analysis of Mexico, since there are no multilevel-multiregional works within a country, just as there is no MuSIASEM analysis for Mexico.…”
Section: Litereature Reviewmentioning
confidence: 99%
“…We should note that there are no studies at the regional level of MuSIASEM inside a country. They exist to compare countries [17][18][19][20][21], to analyze the evolution of a country [22][23][24] or those that exist focus on a specific region [25,26]. For this reason, this work focuses on performing a multilevel and multiregional analysis of Mexico, since there are no multilevel-multiregional works within a country, just as there is no MuSIASEM analysis for Mexico.…”
Section: Introductionmentioning
confidence: 99%